Design and experimental investigation of a low-voltage thermoelectric energy harvesting system for wireless sensor nodes. (15th April 2017) - Guan, Mingjie; Wang, Kunpeng; Xu, Dazheng; Liao, Wei-Hsin
Highlights: A thermoelectric energy harvesting system for wireless sensor nodes is designed. An ultra-low voltage self-startup is implemented. Maximum power point tracking and low power designs are applied for high efficiency. Efficiency of 44.2–75.4% is obtained with open-circuit voltage of 84–400 mV. System efficiency is higher than the commercial BQ25504 converter. Abstract: A thermoelectric energy harvesting system designed to harvest tens of microwatts to several milliwatts from low-voltage thermoelectric generators is presented in this paper. The proposed system is based-on a two-stage boost scheme with self-startup ability. A maximum power point tracking technique based on the open-circuit voltage is adopted in the boost converter for high efficiency. Experimental results indicate that the proposed system can harvest thermoelectric energy and run a microcontroller unit and a wireless sensor node under low input voltage and power with high efficiency. The harvest system and wireless sensor node can be self-powered with minimum thermoelectric open-circuit voltage as 62 mV and input power of 84 μW. With a self-startup scheme, the proposed system can self-start with a 20 mV input voltage. Low power designs are applied in the system to reduce the quiescent dissipation power. It results in better performance considering the conversion efficiency and self-startup ability compared to commercial boost systems used for thermal energy harvesting.